2018
DOI: 10.1002/cncr.31862
|View full text |Cite
|
Sign up to set email alerts
|

Fertility counseling before cancer treatment and subsequent reproductive concerns among female adolescent and young adult cancer survivors

Abstract: BACKGROUND: Fertility counseling before cancer treatment has been advocated by clinical guidelines, though little is known about its long-term impact on the unique reproductive concerns of female adolescent and young adult (AYA) cancer survivors. The goal of this study was to measure the association between fertility counseling by fertility specialists before cancer treatment and subsequent reproductive concerns. METHOD: A cross-sectional analysis was performed among 747 AYA survivors aged 18-40 years who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 42 publications
0
55
1
Order By: Relevance
“…Although FP counseling to individuals facing infertility risks due to cancer treatment has been clearly advocated for over a decade, young patients still report FP as one of the top five unmet needs during their cancer care . Moreover, women obtain more seldom information than men do .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FP counseling to individuals facing infertility risks due to cancer treatment has been clearly advocated for over a decade, young patients still report FP as one of the top five unmet needs during their cancer care . Moreover, women obtain more seldom information than men do .…”
Section: Discussionmentioning
confidence: 99%
“…Although FP counseling to individuals facing infertility risks due to cancer treatment has been clearly advocated for over a decade, 34 young patients still report FP as one of the top five unmet needs during their cancer care. 35,36 Moreover, women obtain more seldom information than men do. 37 Barriers for information provision and access to FP have been acknowledged, in particular low confidence in knowledge from practicing oncologists, 38 Our study is not without limitations.…”
Section: Egg Donation 5mentioning
confidence: 99%
“…18,19 However, recent results in young women with cancer have shown similar results with higher levels of reproductive concerns among those who had used fertility preservation. 41 The authors suggested that these findings could be explained by the increased information about the adverse treatment effects on reproductive potential that this group of women may have received. Although such an explanation could apply also to male patients, previous results have suggested that men perceive sperm banking to be performed in haste and not always after discussion and patient involvement in decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the uncertainty regarding the accuracy of participants' illness‐related worries mirrors their lived experience: It has been noted that cancer survivors' assumptions regarding their fertility as well as potential health risks are based on subjective beliefs rather than medical tests and might be overstated . Participants in our study gave reasons why they did not wish to undergo fertility testing, eg, to avoid assignments of blame.…”
Section: Discussionmentioning
confidence: 98%